Mechanical properties of rCB-pigment masterbatch in rLDPE: The effect of processing aids and water absorption test - Hadi Muhamad Al-Haqqem Abdul; Rahim Nor Azura Abdul; Leng Teh Pei; Wei Chew Kang; Hong Voon Chun; Chun Wong Wee (e-Polymers, 2023)
Homogenization of pigment is the key to coloring a plastic product evenly. In this article, the tensile properties of recovered carbon black merge with low molecular weight lubricants and other compounding ingredients in the form of pigment masterbatch (PM) added in a recycled low-density polyethylene (rLDPE) resin were evaluated. The prepared masterbatch with the varying amount and types of processing aids (A and B) was first compounded using the heated two-roll mill. Subsequently, the manually mixed masterbatch in rLDPE was put through an injection molding machine for the shaping process to produce an rLDPE pigment masterbatch composite (PMC). The tensile test was performed on the samples to evaluate the mechanical properties of the PMC. Meanwhile, the melt flow index test was executed to justify the composite flow characteristics. Fourier-transform infrared spectroscopy analysis and scanning electron microscopy were also carried out to analyze the PM and PMC chemical properties and their constructed surface morphology. Besides, X-ray diffraction analysis was performed to determine the changes in degree of crystallinity before and after the water absorption test. The addition of PM in rLDPE has slightly increased the rLDPE matrix tensile properties. While, the usage of more processing aid B in the PMC has turned out to secure better tensile properties compared to the addition of higher amount of processing aid A in the PMC. Interestingly, the tensile properties of all composites after the water absorption test were enhanced, suggesting that a stronger bond was formed during the immersion period.